Knowledge About Childhood Autism Among Pediatricians, Family Physicians And General Practitioners In Karbala - Hujail, Ali Abdul-Razaq; Al-Shami, Sarah Sabah Hasan; Mohammed, Shaymaa Naser (International Journal of Psychosocial Rehabilitation, 2020)
Autism is a spectrum of neuro developmental disorders occurring early in childhood, that is characterized by persistent deficits/restricted in social communication and interaction; repetitive patterns of behavior; interests, or activities. Commonly, pediatricians and family practitioners are the first health care providers for those families who contact with through routine infant/toddler wellness checks. The aim of the present study was to determine the degree of knowledge about autism among pediatricians, family physicians and general practitioners in Karbala. Also, to assess the factors that may play a role in this knowledge. The study has been conducted at multiple hospitals and primary health care centers at the Holly Karbala city, Iraq. The doctors (n=132) of different age groups, both genders and different specialties (pediatricians, family physicians and general practitioners) was included. A specially designed questionnaire form has been prepared. A socio-demographic questionnaire was used to obtain information. The assessment of the knowledge of participants about the childhood autism revealed that 59.1% participants had good “knowledge about childhood autism among health workers” (KCAHW) score while 40.9% had inadequate KCAHW score. There were statistically significant association between the good KCAHW and older age, the older age participants were more likely to have good KCAHW scores (84.2%) compared to younger age. This supported by the significant association between the good knowledge (18.6±8.8years practice) as compared to inadequate knowledge (15.3 ± 6.4years practice). The significantly longer duration of experience as specialist reported that maximum had good knowledge (11.4 ± 5.4years) than inadequate knowledge (8.8 ± 3.6years) on autism. Good knowledge about autism reported in less than two thirds of participants. Older age participants and those with longer duration of experience had the higher knowledge scores about autism.